2006
DOI: 10.1136/thx.2005.051763
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of antenatal betamethasone on lung function: 30 year follow up of a randomised controlled trial

Abstract: Background: Antenatal betamethasone is routinely used for the prevention of neonatal respiratory distress syndrome in preterm infants. However, little is known of the long term effects of exposure to antenatal betamethasone on lung function in adulthood. Methods: Five hundred and thirty four 30 year olds whose mothers had participated in the first and largest randomised controlled trial of antenatal betamethasone were followed. Lung function was assessed by portable spirometric testing. The prevalence of asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 24 publications
5
29
0
3
Order By: Relevance
“…Thus far, follow-up studies after one course of GCs prenatally in human have been reassuring, and show only subtle neurological impairment at the age of 6, but normal development at the age of 12, 20, and 30 (MacArthur et al, 1982;Schmand et al, 1990;Smolders-De Haas et al, 1990;Dessens et al, 2000;Dalziel et al, 2006). However, our data indicate that more detailed and specific follow-up studies in humans are required, since irreversible long-term adverse effects of GC treatment may occur later in life.…”
Section: Discussionmentioning
confidence: 94%
“…Thus far, follow-up studies after one course of GCs prenatally in human have been reassuring, and show only subtle neurological impairment at the age of 6, but normal development at the age of 12, 20, and 30 (MacArthur et al, 1982;Schmand et al, 1990;Smolders-De Haas et al, 1990;Dessens et al, 2000;Dalziel et al, 2006). However, our data indicate that more detailed and specific follow-up studies in humans are required, since irreversible long-term adverse effects of GC treatment may occur later in life.…”
Section: Discussionmentioning
confidence: 94%
“…In the follow-up studies of the original Liggins cohort (105-110), 30 years later, adults exposed to betamethasone (24 -48 mg total betamethasone dose) as fetuses exhibit more insulin resistance as measured by an oral glucose challenge (107), but the risk of impaired lung function, the prevalence of wheeze and asthma, or the risk of cardiovascular disease were not increased after a single course of betamethasone treatment (105,110). In other follow-up studies, renal function at the age of 19 years was decreased after a single course of fetal betamethasone exposure, although this finding may be confounded by preterm birth rather than the early glucocorticoid exposure, because the risk of chronic renal failure is increased in prematurely born individuals (111).…”
Section: A Clinical Backgroundmentioning
confidence: 98%
“…Fetal and infant safety issues have been addressed, and long-term studies of single-course prenatal corticosteroid treatment have not shown any adverse effects with regard to physical or mental development. [28][29][30][31] This evidence provides reassurance regarding potential concerns about greater prenatal corticosteroid use at 33 and 34 weeks of gestation. It could be argued that such use is likely safer among fetuses at 33 and 34 weeks of gestation, compared with those between 24 and 32 weeks, given the relative maturity of the central nervous system and other organ systems.…”
Section: Discussionmentioning
confidence: 88%